Benign cementoblastoma of posterior mandible in growing patient - Santoshni Samal; Diljith Rishi (Wolters Kluwer Medknow Publications, 2022)
Cementoblastoma is a benign tumor of odontoblastic origin usually associated with pain and swelling and mainly occurs in the mandibular region. It is mainly associated with the roots of premolars and molars in the second and third decades of life. This case describes cementoblastoma in a growing affected person, where its diagnosis and intervention are explained in a 16-year-old male. Cementoblastoma is not so common in pediatric patient. This case reports describe a young growing patient where it is surgically treated keeping this in mind so that it will not affect future growth.